Effect of Adding Oil Palm (Elaeis guineensis Jacq.) Mesocarp Fibers to Cement Composites - Luis Ferroel Gamarra-Romero (Colombia Forestal, 2024)
The construction industry's ongoing pursuit of eco-friendly materials has led to extensive research into fiber cement composites (FCC), particularly those utilizing natural fibers such as oil palm (Elaeis guineensis Jacq.) mesocarp fiber (OPMF) from Peru. This study examined the physical, mechanical, and chemical effects of adding different proportions of OPMF (0, 3, 6, and 9%) in manufacturing FCCs. This addition resulted in reduced values regarding density, porosity, and modulus of rupture, as well as in increased moisture content and thickness reduction. The FCC containing 3% OPMF exhibited the most favorable performance thanks to its higher density and its lower water absorption and porosity when compared to the control board (0%-OPMF). Micro-images revealed minor microcracks and interfacial gaps, indicative of debonding, which compromises the properties of the FCC. Furthermore, an infrared spectrum analysis demonstrated an increase in hydroxyl group vibrations with an increased fiber proportion.